Comparison of position of a heated thin plate located in a cavity for natural convection - Öztop, Hakan Fehmi; Dagtekin, I; Bahloul, A (Pergamon-Elsevier Science Ltd, 2004)
In this numerical study, natural convection heat transfer in a square cavity with a heated plate built-in vertically and horizontally was investigated. In order to obtain finite difference equations, transport and energy equations were integrated based a finite control volume with non-staggered grid arrangement. The discretized equations were solved with TDMA using SIMPLEM algorithm iteratively. The study was performed for different Rayleigh number values ranging from 10(4) to 10(6) and for different aspect ratios and position of heated plate. Air was chosen as a working fluid (Pr=0.71). The effect of the position and aspect ratio of heated plate on heat transfer and flow were addressed. It is found that mean Nusselt numbers at both vertical and horizontal location position increased as Rayleigh number is increased. Further, when the plate is located vertically heat transfer is enhanced about 20% more than for horizontal located position at higher Ra numbers. (C) 2004 Elsevier Science Ltd.
Keywords: Enclosures; Flow